Assessment of Imamī and Mu'tazilī Common Views on Nature of Moral Goodness and Badness and Nasir al-Din al-Tusi's Role - Taleqani SayyedAli; Hossein Rafiei (اخلاق وحیانی)
Many Muslim theologians have examined the nature of moral goodness and badness when discussing divine actions. In the meantime, most of them have defined moral goodness and badness on the basis of other concepts that considered more basic. The most frequent definitions of good and bad in their works can be divided into three general groups: negative definitions, positive definitions and definitions containing elements of divine reward or punishment. On "negative definitions" moral good action is defined using the means of negation (not merited vituperation); but this is not the case in positive definitions. An examination of the historical developments of the definitions by Imamiyyah shows that Nasir al-Din al-Tusi is a turning point in this regard in three respects. The first is that the theologians before him, with the exception of Abu al-Salah al-Halabi, defined the good and the bad negatively, while most theologians after al-Tusi have turned away from negative definitions in an attempt to provide a positive definition or a definition containing reward and punishment. Second, among the Mu'tazilites and the Imamī mutakallimun, al-Tusi was the first theologian to use the elements of divine reward or punishment in one of his definitions; and this definition has given rise to new theoretical discussions among theologians after him. And thirdly, before al-Tusi, the most Mu'tazilī and Imamī theologians used the element of "entitlement", while al-Tusi is the first one who removed the element of "merit" (Istihqaq) in one of his definitions and used the element of "necessity" instead.